Metabolic signature in stage A/B heart failure: A study in asymptomatic Type 2 Diabetes - Brady, Emer M. (2024)
Background: Heart failure with preserved ejection fraction (HFpEF) is a heterogenous multi-system syndrome with limited efficacious treatment options. When coupled with the rising prevalence of Type 2 diabetes (T2D), which predisposes HFpEF, it remains one of the biggest challenges in cardiovascular medicine today. Novel therapeutic targets are required to meet this important clinical need. Deep phenotyping studies including -OMIC analyses can provide important pathogenic information to aid the identification of such targets.